Reward Responsiveness and Inhibition Traits Differentially Predict Economic Biases in Gain and Loss Contexts - Fernandez, Kylie N.; Lighthall, Nichole R. (Frontiers in Psychology, 2019)
Differences in decision making are frequently observed in economic contexts such that risky assets are overvalued in gain conditions, implying optimism, and undervalued in loss conditions, implying pessimism. Previous research suggests that such domain-based biases may depend on individual differences in motivational traits and affective states, but it is presently unclear which of these personal characteristics is most predictive of belief. To address this gap in the literature, we investigated the relative influence of positive and negative motivational traits (general sensitivity to rewards and punishments) versus affective states (current levels of positive and negative emotions) on measures of domain-based biases in beliefs about economic choice options. We also expanded on previous research by examining how the valence of one’s judgment context may determine whether beliefs about risky choices are more strongly influenced by positive versus negative characteristics. Biases in belief were calculated using an economic decision task that involved estimating the relative value of risky “stocks” relative to safe “bonds” from experienced outcomes. Experiment 1 used a positive judgment context (likelihood of a “good stock”) while Experiment 2 used a negative judgment context (likelihood of a “bad stock”). Experiment 1 results indicated that trait-level sensitivity to rewards predicted domain-based biases and suboptimal choice behavior in a positive judgment context, while negative affective state was a relatively weaker predictor of choice behavior alone. Experiment 2 results indicated that trait-level sensitivity to punishment predicted domain-based biases in a negative judgment context. A subsequent cross-study analysis confirmed that high sensitivity to rewards was most predictive of domain-based biases in a congruent, positive judgment context. Collectively, these results suggest that motivational traits have a stronger influence on beliefs about risky choices than affective states, but positive and negative motivations are differentially predictive of biased beliefs depending on the valence of one’s decision context.